Analisis Pengendalian Biaya Produksi Sebagai Suatu Usaha Untuk Meningkatkan Efisiensi Biaya Produksi di PT Padasa Enam Utama Teluk Dalam - Tohang, Uli Nurhaida Br; Silaban, Adanan; Sijabat, Jadongan (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
Increasing production costs will impact company profits. Therefore, production cost control is necessary to prevent cost increases. The continuous decline in monthly profits requires production cost control, especially by optimizing it. This study aims to examine the implementation of production cost control at PT. Padasa Enam Utama Teluk Dalam, and determine the effectiveness of production cost control at PT. Padasa Enam Utama Teluk Dalam in improving production cost efficiency. For this study, the author used a qualitative descriptive method. To obtain the necessary data, the author used two data collection methods: interviews and documentation. The results of the study are based on an analysis of the difference between standard costs and actual costs at PT. Padasa Enam Utama Teluk Dalam from January to December 2024, showing that the standard cost for direct raw materials was Rp -7,381,494,125; direct labor costs were Rp 22,069,487; and factory overhead costs were Rp -4,531,731,018. These values indicate that production cost control has not been implemented optimally, because there are unfavorable differences in several production cost components. Furthermore, production cost efficiency is uneven across components, with raw materials at -44.8%, direct labor at -0.2%, and factory overhead at -17.9%. Therefore, production cost control at PT. Padasa Enam Utama Teluk Dalam has not yet improved production cost efficiency.